Ефективний точний ПДС-алгоритм розв’язання задачі про сумарне запізнювання для одного приладу - Pavlov, A. A.; Misura, E. B. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The effective exact algorithm is presented in this article for total tardiness problem solution when processing independent tasks with due dates on one machine. The algorithm is based on the new approach to the solution of problems with due dates, the main point of the approach is the optimal utilization of untardy jobs' slack times. The algorithm allows to get solutions that are qualitatively grater than known results.